2006
DOI: 10.1080/14786430500479720
|View full text |Cite
|
Sign up to set email alerts
|

TEM study of NbC heterogeneous precipitation in ferrite

Abstract: International audienceThe heterogeneous precipitation of NbC in ferrite has been quantitatively characterised by Transmission Electron Microscopy in a Fe-C-Nb model alloy for different isothermal heat treatments. Elongation and size distribution of precipitates have been derived from Dark Field imaging. For each precipitation states, the precipitation of NbC is occurring on dislocations due to the as-quenched state. This precipitation mechanism leads to characteristic arrays of precipitates in which precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 5 publications
1
19
1
Order By: Relevance
“…4a illustrates another precipitation state in which carbonitride particles are located on dislocations. Recent studies on microalloy precipitates formed in ferrite grains, have shown that they prefer to nucleate heterogeneously on dislocations in order to reduce the strain field which stems from lattice parameter difference between the precipitates and ferrite [25][26][27][28][29].…”
Section: Fine-scale Precipitatesmentioning
confidence: 99%
“…4a illustrates another precipitation state in which carbonitride particles are located on dislocations. Recent studies on microalloy precipitates formed in ferrite grains, have shown that they prefer to nucleate heterogeneously on dislocations in order to reduce the strain field which stems from lattice parameter difference between the precipitates and ferrite [25][26][27][28][29].…”
Section: Fine-scale Precipitatesmentioning
confidence: 99%
“…[33] Perrard et al detected heterogeneous precipitation in ferrite in the temperature range of 1073 K to 873 K (800°C to 600°C) with relatively long isothermal holding. [34] The location of these small precipitates is another important aspect that could be interesting to evaluate. It is reasonable to believe that such precipitates would form on the dislocations or grain boundary junctions.…”
Section: A Microstructural Changesmentioning
confidence: 99%
“…[6,7] During the nucleation stage of the alloy carbides, the dislocation and distinct interface are considered active initiators of the precipitation sequence, because it represents an initial energetically favorable stage to be nucleation sites. [8][9][10] The sophisticated understanding of the nucleation and associated diffusion behaviors of carbon and carbon-forming elements helps to obtain a reasonable explanation of the formation mechanisms of the alloy carbides, and further optimizes service performance at ambient or elevated temperatures by controlling the sizes, morphology, and density of the precipitates in the multicomponent steel.…”
Section: Introductionmentioning
confidence: 99%